Presencia de Escherichia coli, Pseudomona aeruginosa, Staphylococcus spp, en infecciones óticas y su susceptibilidad a los antimicrobianos en caninos en la parroquia de san Bartolo de la ciudad de Quito. - Quishpe Catota, Walter Ruperto (2023)
The aim of the research was to determine the sensitivity of Staphylococcus spp, Pseudomona aeruginosa and E. coli to antimicrobials, which was performed in July-October 2022, from 28 canine swabs at the Biocan Veterinary Clinic in the city of Quito. In the course of the practice, they were sown in culture media in Blood Agar, Mannitol Salt, EMB and Cetrimide and incubated for 24 hours. The next day, the 3 pathogens that grew were inoculated to sow with sterile swab plates with Mueller Hinton, gluing antimicrobial discs and incubating at 37°C for 24 hours, readings were measured with a ruler, Diameters of microbial growth inhibition halos formed on each antibiotic disc. 82% of canine swabs were positive for Staphylococcus spp, 11% for Pseudomona aeruginosa and 7% for E. coli; It is concluded that the antibiotics sensitive for Staphylococcus spp were ciprofloxacin, imipenem, meropenem, chloramphenicol, streptomycin, vancomycin and amoxicine +a. clavulanic, gentamicin, azithromycin, clindamycin, trimethrin and doxycycline. Antibiotics sensitive to Pseudomona were azithromycin and imipenem, ciprofloxacin and gentamicin. For E. coli were meropenem, streptomycin, chloramphenicol, imipenem, ciprofloxacin, doxycycline, clindamycin and amoxicillin + a. clavulanic